Quarter Life Crisis in College Students: How Do Religiosity and Self-Efficacy Affect? - Sholikhah, Thoirotul Mar'atus; Fauzan, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyzw the influence of religiosity and self-efficacy on the quarter-life crisis in final-year college students. The respondents in this study were final-year students of UIN Sayyid Ali Rahmatullah Tulungagung. The study had 323 respondents aged around 20-24 years. The research sample was taken using a non-probability sampling technique, with the respondent criteria being final-year students of the 2019 batch of UIN Sayyid Ali Rahmatullah Tulungagung. We used three instruments: the religiosity scale, self-efficacy scale, and quarter-life crisis scale, that had been declared valid and reliable. The data were tested and analyzed using the classical assumption test and multiple linear regression analysis with partial t-test hypothesis testing and simultaneous F-test. The results of the study showed that religiosity and self-efficacy simultaneously had a significant effect on quarter-life crisis and a negative impact on it, meaning that if there were an increase in religiosity and self-efficacy, the level of quarter-life crisis would decrease. The results of the analysis of the percentage of influence of each variable obtained a percentage value of negative impact on quarter-life crisis of 6.9% on the religiosity variable and 19.6% on the self-efficacy variable. This finding implies that increasing the religiosity and self-efficacy of students can be an effective strategy to reduce psychological stress related to quarter-life crises and can be used as a basis for developing prevention and intervention programs in higher education environments Keywords: religiosity, self-efficacy, quarter life crisis